2012
DOI: 10.3233/jad-2011-111667
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Mild Cognitive Impairment and Alzheimer's Disease in Arabic Villages in Northern Israel: Impact of Gender and Education

Abstract: The prevalence of mild cognitive impairment (MCI) and Alzheimer disease (AD) have not been well been studied in Arab populations. In a door-to-door study of all residents aged ≥65 years in Wadi-Ara, an Arab community in northern Israel, we estimated the prevalence of AD, MCI and the risk of conversion to AD. Subjects were classified as cognitively normal, MCI, AD or other based on neurological and cognitive examination (in Arabic). MCI subjects were re-examined (interval ≥1 year) to determine conversion to AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 46 publications
7
46
1
Order By: Relevance
“…The prevalence of mild cognitive impairment in Taiwan was higher in women than that in men after adjusting for age, education level, and other common associated factors [24]. Similar findings were reported in several other studies [25,26]. Consistent with these studies' results, we found that the prevalence of CIND in northern China was higher in women than in men, with prevalence rates of 26.1% for women and 19.8% for men.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of mild cognitive impairment in Taiwan was higher in women than that in men after adjusting for age, education level, and other common associated factors [24]. Similar findings were reported in several other studies [25,26]. Consistent with these studies' results, we found that the prevalence of CIND in northern China was higher in women than in men, with prevalence rates of 26.1% for women and 19.8% for men.…”
Section: Discussionsupporting
confidence: 81%
“…6,18 Regarding gender, results from the same study showed that while the prevalence rate of AD among men was 15%, among women it reached 25% (this difference was statistically significant at the P < .0005 level). The difference between the genders was even more impressive in the door-to-door study, with prevalence rate estimates among men being 5.2% and among women 14.2%, 8 with the contribution of gender to risk of AD remaining significant following control for education level.…”
Section: Sociodemographic Factorsmentioning
confidence: 92%
“…3 The relatively high prevalence of MCI in this population also predicts patients with AD to be added each year. 8 After examining the literature in this area, we conclude that the topic of AD-its epidemiological, clinical, and societal characteristics-among the Arab population in Israel remains an understudied and poorly understood topic. In fact, a majority of publications assessing the genetic and clinical aspects of the disease were based on 2 studies conducted in the same geographic area-Wadi Ara, which includes mainly Muslim residents.…”
Section: Summary Conclusion and Research Recommendationsmentioning
confidence: 98%
“…Because of differences in racial, sociocultural, and environmental context and in study methodology, large variations in the patterns of cognitive impairment have been found across studies. For example, the prevalence of cognitive impairment ranges from 19.2% to 38% in the USA and from 2.4% to 76.6% in China; its prevalence is 31.2% in Arabic countries and 22.2% in Taiwan . The main correlates of cognitive impairment include low education level, cerebrovascular disease, and advanced age .…”
Section: Introductionmentioning
confidence: 99%